City life in the midst of the forest: a Punan hunter-gatherer’s vision of conservation and development - Levang, P.; Sitorus, S.; Dounias, E. (2007)
The Punan Tubu, a group of hunter-gatherers in East-Kalimantan, Indonesia, are used to illustrate the very real trade-offs that are made between conservation and development. This group has undergone various forms of resettlement in the 20th century, to the point that some are now settled close to the city of Malinau whereas others remain in remote locations in the upper Tubu catchment. This study is based on several years of ethnographic and household analysis. The Punan clearly favor both conservation and development. In the city, the Punan benefit from all positive effects of development. Child and infant mortality rates are very low, and illiteracy has been eradicated among the younger generation. However, the Punan complain that nothing in town is free. The older generation, in particular, resents the loss of Punan culture. Because of frustration and unemployment, young people often succumb to alcoholism and drug addiction. The Punan do not want to choose between conservation and development, between forest life and city life. They want to benefit from the advantages of both locations, to enjoy both free forest products and the positive aspects of modern life, to go wild boar hunting in the morning and watch television in the evening. In short, they want to enjoy city life in the midst of the forest. The same kind of contradiction has led to identity problems. They want to uphold the traditional life of the hunter-gatherer, but at the same time they reject marginalization and seek integration into the larger society. In short, they want integration without loss of identity. The settlement of Sule-Pipa illustrates how some groups have dealt with the contradiction more successfully. Thanks to good organization and charitable donations, they have secured educational facilities and basic health care, and marketing costs are reduced by collectively organized road and river transportation. The economy of the village is thriving, mainly because of the collection of forest products from the primary forest. Remoteness has saved the community from intensive logging, from uncontrolled and excessive exploitation of local forest products by outsiders, and from forest conversion. But few remote communities enjoy the luxury of charitable injections of funds, and roads will be built to the remote locations sooner or later. However, playing for time can help the Punan develop the capacity and ability to cope with a competitive developed world and maintain their cultural identity.